SOCIAL MEDIA ANALYSIS AND SERVICE QUALITY ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY AT PT. KATIGA RITEL STRENGINDO (K3 MART) MEDAN - Jhony; Mesra B; Muhammad Dharma Tuah Putra Nasution (RADJA PUBLIKA, 2025)
The retail industry in Indonesia has undergone a significant transformation, triggered by the penetration of the internet and social media, which have changed consumer behavior. This study aims to analyze how social media and service quality affect customer satisfaction and loyalty at PT. Katiga Ritel Strengindo (K3 Mart) Medan. This study examines the relationship between social media marketing activities, service quality, customer satisfaction, and loyalty using a quantitative approach with a sample of 83 K3 Mart Medan consumers. Data were obtained through a survey and then analyzed using the Partial Least Squares (PLS) method. The results show that social media has a positive effect on customer satisfaction and loyalty, with satisfaction acting as a mediator that strengthens the relationship between social media and loyalty. In addition, service quality has a significant effect on customer satisfaction and loyalty, with satisfaction also acting as a mediator. This study provides a theoretical contribution to enriching the literature on the relationship between social media, service quality, satisfaction, and customer loyalty in the modern retail sector, particularly in the context of lifestyle marts in Indonesia. Practically, the results of this study provide recommendations for K3 Mart management to increase interaction on social media, improve service quality, and improve the physical aspects of the store in order to continuously increase customer satisfaction and loyalty.